Effect Of Calcium Concentration On The Microstructure And Dielectric Properties Of Ca-Doped Plszt (Pb-La-Sr-Zr-Ti) System - Fun, Yan Chin (Universiti Sains Malaysia, 2017)
Lead zirconate titanate (PZT) has perovskite structure and exhibits strong piezoelectric properties. PZT is recently modified by adding dopants to improve the dielectric properties. In this study, the effect of various calcium concentrations on the microstructure and dielectric properties of Ca-doped PLSZT (Pb-La-Sr-Zr-Ti) is investigated. The starting high purity powder is weighed according to the molecular formula Pb0.93-xCaxLa0.02Sr0.05(Zr0.52Ti0.48)O3 with x = 0.00, 0.02, 0.04, 0.06, 0.08 and 0.10. Ca-doped PLSZT was prepared using high planetary ball mill, palletized and sintered at 1200 ºC for 3 hours with heating rate 5 ºC per minute. Characterizations of the samples were carried out by using XRD, SEM and LCR meter which measured from 1 kHz to 1 MHz. XRD results showed that all Ca-doped PLSZT samples present tetragonal and rhombohedral phase whereas SEM results showed that the grain size of the samples was decreased with increasing calcium concentration. However, the grain size began to enlarge at 8 mol% (x = 0.08) of calcium. The density was observed to be decreased with increasing amount of calcium. The dielectric constants and dielectric loss of samples were decreased with the increasing frequency of applied voltage from 1 kHz to 1 MHz. The dielectric constant is increased with the concentration of calcium. Among all the compositions studied, 10 mol% (x = 0.10) of Ca-doped PLSZT ceramic sample showed remarkable dielectric constant.